'Frames of reference' in Victorian England: What Elizabeth Gaskell's North and South reveals about perceptions of the employment relationship. (April 2021) - Gold, Michael
Alan Fox's conceptualisation of 'unitary', 'pluralistic' and subsequently 'radical' frames of reference has been outstandingly influential in the analysis of industrial relations and human resource management since the 1960s. This article demonstrates, however, that these distinctions long predate Fox even though he popularised the terminology. Evidence that observers used comparable frames of reference to categorise perceptions of the employment relationship goes back to the 1830s, and may be found in certain 'condition-of-England' novels that were set amid the social turbulence of the time. This article is based on close examination of one such novel, North and South, by Elizabeth Gaskell. It informs our historical understanding of Fox's concept of 'frames of reference' through exploration of the relationship between three characters who broadly represent employer (unitary), union (radical) and middle-class (pluralist) perspectives. Their discussions about industrial conflict raise dilemmas similar to those analysed in contemporary industrial relations literature: how to forge closer relationships between employers and workers through processes designed to nurture high-trust dynamics while remaining aware of the underlying power imbalances between the two sides resulting from social inequalities of class and wealth.